The antidiabetic effect of methanolic extract of Holarrhena pubescens seeds is mediated through multiple mechanisms of action - AbdulRahman A I Alyahya; Mohammed Asad; Mohammed Sanad Alhussaini; Kamal Eldin Ahmed Abdelsalam; Essa Awad Alenezi (Elsevier, 2023)
Holarrhena pubescens is widely used in Indian and Chinese medicine in the treatment of diabetes. The current work determined the oral hypoglycemic and antidiabetic effects of seed extract in rats. The probable mechanism of action was evaluated in-vitro by α - glucosidase inhibition, glucose metabolism in insulinoma (INS-1) cells to reflect secretion of insulin, and protein glycation inhibition. Its potential for herb-drug interaction was evaluated in the cytochrome P450 3A4 (CYP3A4) inhibition assay. The seed extract increased serum insulin levels and reduced serum blood glucose levels in the oral glucose tolerance test. It also reduced the serum glucose levels in streptozocin-induced diabetes. The extract also inhibited α -glucosidase enzyme activity and demonstrated that it can increase the secretion of insulin from INS to 1-rat insulinoma cell line cells in-vitro in a concentration-dependent manner. However, it had a very weak inhibitory effect on protein glycation and it did not affect the activity of CYP3A4. The results of the study showed that H. pubescens seed extract increases insulin secretion and inhibits glucose absorption both in-vivo and in-vitro with a weak protein glycation inhibitory effect. The herb is devoid of CYP3A4 inhibitory effect indicating that it may not have pharmacokinetic interaction with the drug metabolized by this enzyme.